Verb Conjugation Suffixes in Esad Naib’s “Zamanin Eli” Poetry Book - Beg Zade, Kosret Bapir Maghdid; Mirani , Karwan Rauf Taha; Hussein, Selan Neamat (Zanco Journal of Human Sciences, 2024)
Esat Naip, who is considered as one of the famous poets in Iraqi-Turkmen literature, initially published his poems in Kirkuk, Afak, Necme, Beşir and İleri newspapers. In the following periods, he published his poems in the magazine Kardeşlik and some of them in the magazines Yeşil Ada and Fuzuli, which were published in Turkey. (Kerkük Nükteleri, Yapraklar, Armağan, Zamanın Eli) are the poet's written verse and prose works. He also brought together many unpublished poems under the name of (Keşkül). Our study is based on Esad Naib's (Zamanın Eli) poetry book and the verb conjugation suffixes used in selected poems are evaluated. In Turkish: We have two types of moods: 1. İndicative (news) moods, 2. Subjunctive moods. In addition, shows the similarity in Iraqi Turkmen and Turkey Turkish in form and structure. Thus, it is aimed to determine the verb conjugation affixes in the selected (Okuyuculara, Zamanın Eli, En Azizime, Çözülmeyen Bağ, Hancı, Hancı ile Baş Başa, Şölen Salonu) poems of the poet poetry book.